2006
DOI: 10.1111/j.1365-2109.2006.01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypo- and hyper-saline conditions on osmolarity and fatty acid composition of juvenile shrimp Litopenaeus vannamei (Boone, 1931) fed low- and high-HUFA diets

Abstract: Litopenaeus vannamei (Boone) grown in ponds are exposed to salinities of less than 5 g L−1 during inland shrimp culture or to more than 40 g L−1 from evaporation and reduced water exchange in dry, hot climates. However, dietary requirements for shrimp grown in low or high salinities are not well defined, particularly for fatty acids. Feeding shrimp postlarvae with highly unsaturated fatty acids (HUFA) enhances tolerance to acute exposure to low salinity, as a result of better nutritional status, or/and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
3
17
1
5
Order By: Relevance
“…In the present study, there is no significant difference in Na + K + -ATPase activity of gill tissue among the treatments, which is comparable with the studies of Hurtado et al (2006) who concluded Na + K + -ATPase activity is not affected by either diet or salinity. In contrast, it was demonstrated that the composition of ions in the serum varied in accordance with the dietary levels of minerals and this regulation pattern had been noticed among other penaeid species also (Dall & Smith, 1981;Cheng & Liao, 1986).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, there is no significant difference in Na + K + -ATPase activity of gill tissue among the treatments, which is comparable with the studies of Hurtado et al (2006) who concluded Na + K + -ATPase activity is not affected by either diet or salinity. In contrast, it was demonstrated that the composition of ions in the serum varied in accordance with the dietary levels of minerals and this regulation pattern had been noticed among other penaeid species also (Dall & Smith, 1981;Cheng & Liao, 1986).…”
Section: Discussionsupporting
confidence: 81%
“…The dietary supplementation with long‐chain polyunsaturated fatty acids (LC‐PUFA), cholesterol, phospholipids and antioxidant nutrients has shown the most promising results in counteracting the negative effects of extreme salinities in L. vannamei culture (Gong et al., ; Hurtado et al., ; Liu, Wang, Wang, Wang, & Sun, ), although opposing evidence also exists (Hurtado et al., ; Roy et al., ). The role of these compounds in the osmoregulatory mechanisms is mainly supported by changes in cell membrane composition, improved gill membrane permeability, antioxidant system support and increased energy contribution (Liu et al., ; Paula, Volkov, Van Hoek, Haines, & Deamer, ).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity has a significant effect on metabolism of penaeid shrimp (Rosas et al 2001, Zhu et al 2006, Valdez et al 2008. As salinity deviates from the iso-osmotic point, the osmotic balance in shrimp is modified and it expends more energy on osmoregulation and less on growth (Hurtado et al 2006). Shrimp are excellent osmoregulators if ionic ratios in the water are adequate (Gong et al 2004b, Roy et al 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition of shrimp reared at low salinity improved growth and survival by adjusting levels of nutrients in the feeds (Gong et al 2003, 2004a, Perez-Velazquez et al 2007. When shrimp are exposed to low salinity, they have to counteract passive loss of Na + and Cl -by active uptake of Na + from the water in exchange for H + , which occurs in the apical membrane of the osmoregulatory cells to improve their osmoregulatory capacity (Palacios et al 2004, Bückle 2006, Hurtado et al 2006.In arid and semi-arid climates, where high evaporation of pond water is common, salinity can increase to 50psu or higher, especially by the end of the growing season; despite that extreme variation, whiteleg shrimp survive and grow at high densities because of its capacity to regulate variations in osmotic and ionic conditions that permits it to inhabit waters ranging from 0.5-60psu (Roy et al 2007, Jaime-Ceballos et al 2008, Valdez et al 2008. Additionally, the species is resistant to several diseases (Ponce-Palafox et al 1997, Lin et al 2006.…”
mentioning
confidence: 99%